Pipe Stress Analysis of the Steam Pipe of Project Tidore Power Plant (2 X 4 MW) Using CAESAR II - Franky Pasaribu; Johny Wahyuadi Mudaryoto; Robert H Pasaribu (MBI, 2026)
Pipe stress analysis is an important step to ensure that the piping system can function properly and safely. The main goal is to ensure that the piping design can withstand the pressure and load without failure. This analysis follows the guidelines of ASME B31.1 Power Piping, which regulates the design and construction of piping in a Power Plant. The analysis was performed using software Caesar II. This software helps clip various working conditions and measure the pressure in the piping system. From the analysis report, no overstress problems were found in the steam piping line. Since the system already meets ASME B31.1 standards, no changes were needed to the number, position, or type of pipe supports.